The Combined Effects of Tai Chi, Resistance Training, and Diet on Physical Function and Body Composition in Obese Older Women - S. A. Maris; D. Quintanilla; A. Taetzsch; A. Picard; J. Letendre; L. Mahler; I. Lofgren; F. Xu; M. J. Delmonico (Journal of Aging Research)
Obesity is a major health problem in the USA, especially in minority populations over the age of 60 years, and the aging process can cause adverse effects on physical function. Previous research has shown that Tai Chi, resistance training (RT), and diet result in overall health improvements. However, the combination of these specific interventions has yet to be translated to obese older women in an urban setting. The purpose of this study was to examine a combined intervention on the primary outcomes of physical function and body composition. Using a nonrandomized design, 26 obese women (65.2±8.1 years) completed a 12-week intervention; participants were assigned to an intervention (EXD) group or a control (CON) group. The EXD group (n=17) participated in Tai Chi, RT, and a dietary session. The CON group (n=9) was asked to continue their normal lifestyle. Timed up and go (TUG) time was reduced by 0.64±2.1 seconds (P=0.04) in the EXD group while the CON group saw a borderline significant increase of 0.71 sec (P=0.051). The combined intervention helped improve performance on TUG time, but there were no significant increases in other body composition or function measures.